Cam impingement of the hip: a risk factor for hip osteoarthritis. - Agricola, R; Waarsing, J; Arden, N; Carr, A; Bierma-Zeinstra, S; Thomas, G; Weinans, H; Glyn-Jones, S (2013)
Femoroacetabular impingement (FAI) is characterized by abnormal contact between the proximal femur and the acetabulum. Two subtypes have been described: pincer impingement, caused by an overcovered acetabulum; and cam impingement, which occurs as a result of an aspherical femoral head (cam abnormality). A strong correlation exists between cam impingement and the subsequent development of hip osteoarthritis (OA). Major cam abnormalities confer a high risk of OA. However, the association between cam abnormalities and the pathology of OA has been difficult to compare between studies, as different methods have been used to define the abnormality. Cam abnormalities are acquired during skeletal growth and could be influenced by high impact sporting activities. Preventative treatments aiming to reduce the incidence of cam abnormalities and subsequent OA could, therefore, be developed. In this Perspective, we discuss the current understanding of FAI, focusing on cam abnormalities and their association with OA.